KETERAMPILAN DRIBBLING BOLA BASKET - Kurnia, Dedi (Jurnal Olahraga, 2016)
The purpose of this study is to determine the relationship between eye-hand coordination, agility and self-confidence with basketball dribbling skills. The research method used in this study is correlational. The object of this research is all Puragabaya / SMA / SMK students who take basketball extracurricular activities. The independent variable is eye-hand coordination (X1), agility (X2), and self-confidence (X3). While the dependent variable is the basketball dribbling skill (Y). The results of this study are: First, there is a positive and significant correlation between X1 and Y with a correlation coefficient of 0.76 and a determination index of 58.0%. Second, there is a positive and significant correlation between X2 and Y with a correlation coefficient of 0.81 and a determination index of 65.0%. Third, there is a positive and significant correlation between X3 and Y with a correlation coefficient of 0.73 and a determination index of 53.0%. Fourth, there is a positive and significant relationship between X1, X2 and X3 with Y, with a correlation coefficient of 0.83 and a determination index of 68.4%. It can be concluded that basketball dribbling skills can be improved by practicing eye-hand coordination, agility and self-confidence.